Implementasi NodeMCU Esp8266 pada Alat Pelacak Kendaraan Menggunakan Global Positioning System dan MiFi Berbasis IoT - Lestari, Khotifah Puji; Lindawati, Lindawati; Sholihin, Sholihin (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2023)
The vehicle tracking device employs Global Positioning System (GPS) and MiFi-based Internet of Things (IoT) technology and is supplied with security features by the Kodular-developed GPS Tracker application. The implementation consists of a system that combines GPS, MiFi, and IoT technologies to monitor the vehicle's position using coordinate points on a periodic basis. The incorporation of Internet connectivity into a vehicle ensures optimal system performance, which can be monitored using the NodeMCU ESP8266 microcontroller module. In this research, a tracking device was designed using a microcontroller and a smartphone application. The implementation of IoT facilitates device-to-smartphone application for communication. Consequently, based on the design outcomes, motor vehicles are able to determine their position and regulate the passage of electricity to the engine using a relay. This application enables remote monitoring and control of the vehicle's functions by the smartphone application, providing a practical and effective solution for vehicle tracking. The testing results include various distances used to compare the longitude and latitude of the coordinate points, resulting in accurate monitoring system outcomes and facilitating vehicle inspections if it is stolen or under certain conditions.